PENGARUH PERSEPSI PRODUK/PESAN, SUMBER MODEL DAN AFTER SALES TERHADAP MINAT BELI PRODUK DELL DI KOTA YOGYAKARTA - Suharti Sugiyanto; Suharti Suharti (Universitas Sarjanawiyata Tamansiswa, 2018)
This study aims to determine the effect of product / message perception, perception after sales, source model of buying interest.The population in this research is all consumer of Dell product in Yogyakarta city. Samples used 100 responden, this is because this research there are 20 items of dependent and independent variable, then the number of samples taken is 20 x 5 that is 100 samples. The technique for taking samples, is non-probability sampling. Method of taking data using questioner. The analysis technique used is multiple linear regression with 5% significance level.The results of the research obtained the regression equation as follows: Y = 0.216X1 + 0.217X2 + 0.373X3. The perception of product / message has a positive and significant effect on buying interest. Perceptions of model sources have a positive and significant impact on buying interest. The perception of after sales has a positive and significant effect on buying interest. Product / message perception variables, model source perceptions and after-seles perception have an effect simultaneously on buying interest. Buying interest (Y) can be influenced by product / message perception, model source perception and after-seles perception of 33.1%. While the rest equal to 66.9% influenced by other factors